Genome-Wide DNA Methylation Analysis of Soybean Curled-Cotyledons Mutant and Functional Evaluation of a Homeodomain-Leucine Zipper (HD-Zip) I Gene GmHDZ20 - Yang, Hui; Yang, Zhongyi; Mao, Zhuozhuo; Li, Yali; Hu, Dezhou; Li, Xiao; Shi, Guixia; Huang, Fang; Liu, Baohui; Kong, Fanjiang; Yu, Deyue (Frontiers in Plant Science, 2021)
DNA methylation is a major, conserved epigenetic modification that influences many biological processes. Cotyledons are specialized tissues that provide nutrition for seedlings at the early developmental stage. To investigate the patterns of genomic DNA methylation of germinated cotyledons in soybean (Glycine max) and its effect on cotyledon development, we performed a genome-wide comparative analysis of DNA methylation between the soybean curled-cotyledons (cco) mutant, which has abnormal cotyledons, and its corresponding wild type (WT) by whole-genome bisulfite sequencing. The cco mutant was methylated at more sites but at a slightly lower level overall than the WT on the whole-genome level. A total of 46 CG-, 92 CHG-, and 9723 CHH- (H = A, C, or T) differentially methylated genes (DMGs) were identified in cotyledons. Notably, hypomethylated CHH-DMGs were enriched in the gene ontology term “sequence-specific DNA binding transcription factor activity”. We selected a DMG encoding a homeodomain-leucine zipper (HD-Zip) I subgroup transcription factor (GmHDZ20) for further functional characterization. GmHDZ20 localized to the nucleus and was highly expressed in leaf and cotyledon tissues. Constitutive expression of GmHDZ20 in Arabidopsis thaliana led to serrated rosette leaves, shorter siliques, and reduced seed number per silique. A yeast two-hybrid assay revealed that GmHDZ20 physically interacted with three proteins associated with multiple aspects of plant growth. Collectively, our results provide a comprehensive study of soybean DNA methylation in normal and aberrant cotyledons, which will be useful for the identification of specific DMGs that participate in cotyledon development, and also provide a foundation for future in-depth functional study of GmHDZ20 in soybean.